2022
DOI: 10.48077/scihor.25(11).2022.20-30
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sitophilus oryzae on biological properties of Mycobacterium bovis

Abstract: The active spread of tuberculosis around the world has been an urgent issue for many decades, but even now, there is no data on all available methods of introducing the pathogen into a previously healthy territory and the mechanisms of mycobacteria activity, and this makes it impossible to eradicate the disease completely. The purpose of this study was to determine the effect of the rice weevil (lat. Sitophilus oryzae) on the dissociative forms of mycobacterium tuberculosis, their viability, biochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Studies by many authors have confirmed that insects are transmitters of numerous microorganisms (Zarei et al, 2018, Tkachenko et al, 2021aZazharskyi et al, 2022). Sarwar (2015) reported that up to 85% of the cases of infectious diseases have been caused by arthropods that are able to spread pathogens through stings and bites and mechanically via body surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by many authors have confirmed that insects are transmitters of numerous microorganisms (Zarei et al, 2018, Tkachenko et al, 2021aZazharskyi et al, 2022). Sarwar (2015) reported that up to 85% of the cases of infectious diseases have been caused by arthropods that are able to spread pathogens through stings and bites and mechanically via body surface.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we observed changes in enzymatic activity, oriented at survival of mycobacteria in a new environment. Passage through the organism of beetles did not restore pathogenic properties of avirulent strains (Tkachenko et al, 2021;Zazharskyi et al, 2022). However, there are no data about effect on biological properties of a virulent strain of mycobacteria, which poses the main threat to the wellbeing of populations of agricultural animals.…”
Section: Introductionmentioning
confidence: 99%
“…Serum samples of animals exposed to various doses of gamma rays were selectively examined (10 samples taken before and after infection) to detect tissue autoantibodies in the passive hemagglutination reaction (PHGR) according to Boyden with tissue antigens manufactured in this study according to the method of Ye.F. Chernushenko (Zazharskyi et al, 2022).…”
Section: Figure 1 Mycobacteria Of the M Bovis Production Strain Stick...mentioning
confidence: 99%
“…Serum samples of animals exposed to various doses of gamma rays were selectively examined (10 samples taken before and after infection) to detect tissue autoantibodies in the passive hemagglutination reaction (PHGR) according to Boyden with tissue antigens manufactured in this study according to the method of Ye.F. Chernushenko (Zazharskyi et al, 2022).…”
Section: Figure 1 Mycobacteria Of the M Bovis Production Strain Stick...mentioning
confidence: 99%